Quantitative analysis of walking in patients with knee osteoarthritis: a method of assessing the effectiveness of non-steroidal anti-inflammatory treatment. Issue 12 (December 1990) - Blin, O; Pailhous, J; Lafforgue, P; Serratrice, G
Abstract : Most therapeutic tests of osteoarthritis treatments are assessed by criteria based either on fundamental data or on clinical data, which is often subjective. A quantified analysis of locomotion can be used to determine the spatiotemporal indices (stride length and duration), kinematic indices (walking speed, velocity peak), and symmetry criteria that are relevant to the assessment of locomotor handicaps in patients with osteoarthritis. This study examined the progression of locomotor abilities in 11 subjects aged 49-69 (mean 60.9) years with knee osteoarthritis before and after treatment with a non-steroidal anti-inflammatory drug. Naproxen sodium (1100 mg) was given once a day for seven days. The condition before and after treatment was evaluated by quantitative analysis of locomotion, estimation of pain on a visual analogue scale, and assessment of the degree of functional disability. Significant improvement in locomotor indices (proportional increase in walking speed 17.8%) and in degree of pain (proportional decrease 27%) as estimated on the analogue scale was found after non-steroidal anti-inflammatory drug treatment. The lack of a significant correlation between the decrease in pain experienced by the patients and the objective improvement of their functional capabilities emphasises the need in further studies of new treatments to accompany the patients' own assessments of self improvement with a quantitative analysis of the way in which they walk.